How Do Training Centers Prepare a Skilled Workforce? - Batilmurik, Ridolof; Batilmurik, Ridolof Wenand (Public Policy, 2024)
The objectives of this study are to examine the functions and roles of the Vocational Training Institute in Keerom Regency, Papua Province, as well as the challenges and specific constraints it faces. This exploratory research uses a qualitative descriptive method and includes insights from three key informants. Findings reveal that labor institutions play a crucial role in determining workforce quality and professionalism. To support this, adequate facilities and infrastructure are essential to train skilled workers in alignment with labor market demands, reducing employer challenges. Despite a high labor supply, many workers lack the skills needed for available jobs, contributing to regional unemployment. The study also identifies both internal and external barriers requiring focused attention from the Keerom Regency Government. Future research should investigate training program quality using a quantitative approach.